2022
DOI: 10.3389/fendo.2022.925206
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Kisspeptin in the Control of the Hypothalamic-Pituitary-Gonadal Axis and Reproduction

Abstract: The discovery of kisspeptin as a critical central regulatory factor of GnRH release has given people a novel understanding of the neuroendocrine regulation in human reproduction. Kisspeptin activates the signaling pathway by binding to its receptor kisspeptin receptor (KISS1R) to promote GnRH secretion, thereby regulating the hypothalamic-pituitary-gonadal axis (HPG) axis. Recent studies have shown that kisspeptin neurons located in arcuate nucleus (ARC) co-express neurokinin B (NKB) and dynorphin (Dyn). Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 179 publications
0
38
0
2
Order By: Relevance
“…Expression of the kiss1 and kiss1ra genes has also been reported in brain neurons 41 as well as in organs such as the testes, ovaries, pituitary, and pancreas 42 . Kisspeptin increases the secretion of gonadotropins, but for this purpose, it must first stimulate GnRH-producing neurons in the hypothalamus, which must increase Kiss1 receptors on their cell membrane to be stimulated 43 , 44 . Therefore, the action of kisspeptin requires the expression and presence of kiss1ra in GnRH-producing neurons 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the kiss1 and kiss1ra genes has also been reported in brain neurons 41 as well as in organs such as the testes, ovaries, pituitary, and pancreas 42 . Kisspeptin increases the secretion of gonadotropins, but for this purpose, it must first stimulate GnRH-producing neurons in the hypothalamus, which must increase Kiss1 receptors on their cell membrane to be stimulated 43 , 44 . Therefore, the action of kisspeptin requires the expression and presence of kiss1ra in GnRH-producing neurons 41 .…”
Section: Discussionmentioning
confidence: 99%
“…KISS1R is expressed in various brain tissues including the hypothalamus and pituitary. 36 The kisspeptin‐KISS1R system is believed to act directly on GnRH neurons in the preoptic area and infundibular nucleus to produce pulsatile GnRH secretion. 23 , 36 Animal studies confirmed that most GnRH neurons express KISS1R (Figure 1 ).…”
Section: Genetic Variants Of Gpcrs Associated With Pubertal Disordersmentioning
confidence: 99%
“…GnRH is a peptide consisting of 10 amino acids and is encoded by a gene located on chromosome 8. 7) In the fetus, at 14 weeks of gestation, neurons containing GnRH exist in the hypothalamus, As the hypothalamus-pituitary portal system develops, GnRH in the hypothalamus reaches the gonadotroph in the pituitary gland. At 20 weeks of pregnancy, LH and FSH are secreted by the pituitary gland.…”
Section: Normal Physiology Of the Reproductive Axismentioning
confidence: 99%